A Rasch Analysis of the Substance Abuse Subtle Screening Inventory–3. Issue 1 (7th April 2013) - Hill, Tara M.; Laux, John M.; Stone, Gregory; Dupuy, Paula; Scott, Holly
<x xml:space="preserve">Abstract</x> Rasch analysis of the Substance Abuse Subtle Screening Inventory–3 (SASSI‐3; F. G. Miller & Lazowski, 1999) indicated that the SASSI‐3 meets fundamental measurement properties; however, the authors of the current study recommend the elimination of nonfunctioning items and the improvement of response options for the face valid scales to increase functioning and ease of use.